‘They overworked us’: Humiliation and claims to recognition of volunteer nurses in the aftermath of the Ebola epidemic in Sierra Leone (Medicine Anthropology Theory, 2017)
In this article, I describe the institutional humiliation experienced by volunteer nurses in Sierra Leone following the end of the Ebola epidemic. They had been promised formal employment with the Ministry of Health and Sanitation after working in the Ebola treatment units in the country, but were dismissed from the hospitals where they were volunteering and felt humiliated. I suggest that this maltreatment of volunteer nurses cannot be grasped through the existing categories and parameters used by global health policies nor through conventional moral theories that inform our understandings of global health. Instead, we need to attend to the harm inflicted upon the volunteer nurses’ sense of self-respect through institutionalized forms of subordination and misrecognition. Drawing on philosophical and anthropological works on recognition, I argue that we should pay attention to moral emotions as distinct objects of study to grasp how those who are humiliated register and validate the maltreatment they have undergone.